THE EFFECTIVENESS OF DIGITAL GAMES IN ENGLISH AS A FOREIGN LANGUAGE (EFL) INSTRUCTION (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The usefulness of incorporating digital games—such as educational applications, virtual worlds, and gamified platforms—into English as a foreign language (EFL) class is examined in this study. The study investigates how these resources affect students' vocabulary growth, reading comprehension, motivation, and general involvement. Learner feedback questionnaires and experimental group comparisons in elementary and intermediate EFL classes were used to gather data. Although issues like content selection and technology accessibility still exist, research indicates that digital games greatly boost students' motivation and offer a low-stress, immersive setting for language practice, resulting in improved learning outcomes.